Microcredit Regulation in South Africa: A Comparative Study of the Law in Context - Wrigley, Lauren Kate (Department of Commercial Law, 2020)
In this dissertation I shall highlight the shortcomings of the microcredit regulations in the NCA to develop proposals that ensure that the microfinance regulatory framework is not only made sensible on paper but in practice. Furthermore, it is hoped that these proposals will reflect a prosperous reality for South Africa’s socio-economic context, at present and in the future. Through analysing South Africa’s unique context, and drawing on experiences of the microcredit industry in Bangladesh (a similar developing country), I shall contribute to South Africa’s policy framework in making recommendations on amendments. These recommendations will support the objective of giving effect to the aims of the NCA relating to equally accessible and responsible credit and in ensuring that the social and economic welfare of South African citizens are advanced. Research into this topic is essential for two reasons: The first reason is that it is a necessary contribution to the literature on microfinance in South Africa. Not only will this dissertation focus on highlighting all the main aspects of microcredit regulation in South Africa, but it will also tell a cohesive story from the introduction of microcredit regulation to present-day recommendations on the improvements of such. The second reason is that this dissertation will contribute to policy reform in South Africa, intended to be a feed for further research and action on creating amendments to the microcredit policy framework. In sum, this dissertation will have both theoretical and practical significance.